2006
DOI: 10.3363/prb.20.129
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Adsorption Properties of Hydroxyapatite Surface-Modified by Cetylphosphate

Abstract: Hydroxyapatite (HAP) was prepared from CaCl 2 , Na 2 HPO 4 and NaOH in an aqueous phase mixed with a chloroform solution of cetylphosphate (CP). The CP was incorporated mainly on the surface of HAP but not to its bulk phase, resulting in formation of a hydrophobic surface. This surface-modified HAP has various characteristic properties different from those of the intact HAP. Some of the examples are as follows; an increase in a contact angle of water droplet, a decrease in a mean diameter of the HAP particle, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The change of pH pattern in deionized water can be explained in terms of a high affinity of nHAp for water [ 31 ]. In water, the hydrolysis of nHAp predominates causes an increase in pH, and might have initially restricted the hydrolysis of PLA [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The change of pH pattern in deionized water can be explained in terms of a high affinity of nHAp for water [ 31 ]. In water, the hydrolysis of nHAp predominates causes an increase in pH, and might have initially restricted the hydrolysis of PLA [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Taking PLA as a structural biocompatible (and mostly bioinert) base for a composite, hydroxyapatite (HAp) was selected as a potential bone-regenerating functionalisation agent. HAp offers micro-scale particulates and thermal-stability at the processing temperatures of PLA 3D-printing filament extrusion and FFF, a consistent affinity for organic molecules, and documented osteoconductive properties [6,[46][47][48][49][50]. The current study will present results from the development for a method for thorough integration of HAp particles into a PLA matrix in the form of a 3D-printable filament.…”
Section: Introductionmentioning
confidence: 96%
“…HAP modified with cetylphosphate revealed that the higher the initial concentration of CP in a chloroform solution, and the higher the surface concentration of CP on HAP, the greater the contact angle of water [31]. This means that water droplets had difficulty spreading on the particle and would minimize their contact with the surface of the CPmodified HAP due to the hydrophobic tails of the CP on the CP-HAP surface.…”
Section: Modifier Polarity and Hydrophobicitymentioning
confidence: 93%
“…The resulting CP-mHAP has a hydrophobic surface and a decrease in particle diameter [31]. This modification also increased the surface adsorption for organic compounds such as sodium p-dodecylbenzenesulfonate (SDBS) because of an interaction between the alkyl chains of SDBS and the CP-modified HAP surface [31].…”
Section: Co-precipitationmentioning
confidence: 98%
See 1 more Smart Citation